Progressive Collapsing Foot Deformity Classes Correction after Isolated Arthroscopic Anterolateral Subtalar Arthrodesis - Alessio Bernasconi MD, PhD; Matthieu Lalevée MD; Céline Fernando PhD; Antonio Izzo MD; Cesar de Cesar Netto MD, PhD; François Lintz MD, PhD (Foot & Ankle Orthopaedics)
Category: Hindfoot; Midfoot/Forefoot Introduction/ Purpose: Subtalar osteoarthritis in the context of flatfoot recently renamed Progressive Collapsing Foot Deformity (PCFD) may be treated through subtalar joint (SJ) arthrodesis with anticipated consequences on three-dimensional bony configuration. This study investigates the correction of PCFD-related deformities achieved after Anterolateral Arthroscopic Subtalar Arthrodesis (ALAPSTA). Methods: In this retrospective study, we evaluated pre- and post-operative (at 6 months) weight bearing computed tomography (WBCT) images of patients diagnosed with PCFD with a degenerated SJ (2A according to PCFD classification) and/or peritalar subluxation (2D) with or without associated flexible midfoot and/or forefoot deformities (1B, 1C and 1E) which underwent ALAPSTA as a standalone procedure between 2017 and 2020. Multiple measurements were used to assess and compare pre and post-operative PCFD classes. Results: Thirtythree PCFD (33 patients, median age 62) were included. Preoperative medial facet subluxation was 28.3%. Overall PCFD 3D deformity improved with a reduction of the foot and ankle offeset from 9.3 points to 4 (p< 0.001). Class A (hindfoot valgus, measured through the tibiocalcaneal angle, the calcaneal moment arm, the calcaneal offset and the hindfoot angle), class B (midfoot abduction, measured using the talonavicular coverage angle and the axial talo-first metatarsal angle) and class C (forefoot varus, measured through the sagittal talo-first metatarsal angle and the forefoot arch angle) significantly improved after surgery (p< 0.001 for all measurements). No patient had a valgus deformity at the ankle pre-operatively (therefore no patient presented with class E), and no significant change of the talar tilt was observed (p=0.12). Conclusion: In this series, ALAPSTA performed as a standalone procedure to treat patients diagnosed with PCFD with a degenerated subtalar joint and/or peritalar subluxation was effective not only at correcting hindfoot alignment but also flexible midfoot abduction and flexible forefoot varus.